Access to healthcare services for people with non-communicable diseases during the COVID-19 pandemic in Ibadan, Nigeria: a qualitative study - Lucia Yetunde Ojewale; Ferdinand C. Mukumbang (BMC, 2023)
Abstract Background Desirable outcomes for people with non-communicable diseases (NCDs) are achieved when they access routine monitoring and care services. Expectedly, the COVID-19 pandemic severely impacted access to healthcare services, leading to poor health outcomes among people with NCDs. We aimed to [1] explore the delays in accessing healthcare services and [2] understand alternative actions adopted by people with NCDs to overcome these delays. Methods We conducted an exploratory qualitative research guided by the "Three Delays" model to unpack the barriers to healthcare access for people living with NCDs in Ibadan, Nigeria. The "Three Delays" model conceptualizes the reasons for negative/adverse healthcare outcomes related to the patient's decision-making to seek healthcare, reaching an appropriate healthcare facility, and receiving adequate care at the healthcare facility. Twenty-five (25) people with NCDs were purposively selected from the University College Hospital's medical outpatient department to participate in in-depth interviews. Interview recordings were transcribed verbatim and analyzed using a deductive-inductive hybrid thematic analysis. Results At the level of individual decision-making, delays were related to fear of contracting COVID-19 in the hospital (considered a hotspot of the COVID-19 pandemic). Regarding reaching an appropriate healthcare facility, delays were mainly attributed to the intra- and inter-city lockdowns, limiting the movements of persons. For those who successfully arrived at the healthcare facilities, delays were related to the unavailability of healthcare professionals, prioritization of COVID-19 patients, and mandatory adherence to COVID-19 protocols, including COVID-19 testing. To overcome the delays mentioned above, people with NCDs resorted to (i) using private healthcare facilities, which were more costly, (ii) using virtual consultation through mobile phone Apps and (iii) self-management, usually by repeating previously prescribed prescriptions to obtain medication. Conclusion Pandemic conditions provide unique challenges to people with chronic illnesses. Recognizing the need for continuous access to monitoring and care services under such conditions remains critical. Alternative health service provision approaches should be considered in pandemic situations, including remote healthcare services such as Mobile health apps (mHealth) that can help manage and prevent NCDs.